Large eddy simulation of passive scalar transport in a high Schmidt number turbulent incompressible wake with experimental validation. (1st December 2015) - Jansen, Katrine M.; Kong, Bo; Fox, Rodney O.; Hill, James C.; Olsen, Michael G.
Abstract: Large eddy simulation of the passive scalar transport in a high Schmidt number turbulent confined wake flow has been performed. The results are evaluated by comparison to particle image velocimetry (PIV) and planar laser-induced fluorescence (PLIF) data, including point-wise data as well as spatial correlations. In the LES simulations, the gradient diffusion hypothesis is used to close the transport equation for the passive scalar. Different discretization schemes are investigated in order to determine the best choice for ensuring boundedness of the passive scalar and to accurately predict the mixing rate. The simulation results compare well to experimental data, demonstrating that the transport mechanisms in this high Schmidt number turbulent flow are well predicted by the LES method. Two-point spatial correlations of passive scalar with velocity predicted by the simulation show good agreement with the experimental results, indicating that the turbulent coherent structures of the flow are reproduced by the simulation. Abstract : Highlights: LES is performed for passive scalar mixing in a high Schmidt number turbulent wake. The simulation is validated against PIV and PLIF data. Detailed comparisons of one-point statistics and spatial correlations were made. LES compared well with experiments, thus the transport mechanisms were well simulated. Two-point spatial correlations of passive scalar with velocity showed good agreement.